Alteration of azurite into paratacamite at the St. Alessandro Church (Lasnigo, Italy) - Giovanni Cavallo (Conservar Património, 2009)
Many case studies report the alteration of the pigment azurite into paratacamite on wall paintings in Europe (for instance in Italy, Portugal, Austria). The analytical research performed on the 16th century wall paintings in the St. Alessandro church at Lasnigo (North Italy) pointed out an irregular and inhomogeneous alteration of azurite. It is well known that azurite can transform into malachite when the humidity is high and in alkaline conditions and into basic copper chlorides (atacamite, paratacamite, clinoatacamite) when solutions containing chlorine ions are present. X-ray diffraction allowed to refer the green compounds to paratacamite. The remaining surfaces painted with azurite do not reveal any trace of alteration despite of the presence of chlorine; a few traces of azurite have been found inside the direct incisions of the Crucifixion painted scene where the original blue pigment was completely lost. The microclimatic conditions seem to play an important role in the process in addition to the presence of water and chlorides. The surface where alteration occurs is the only one to be cyclically heated by the solar radiation, causing the transport of the solutions containing chlorides. The relationship between the environment and the chemical processes occurring represents an important issue to be developed.